Optimization of Protein Quality Assay in Normal, opaque-2, and Quality Protein Maize - Kaur, Charanjeet; Singh, Alla; Sethi, Mehak; Devi, Veena; Chaudhary, Dharam Paul; Phagna, Ramesh Kumar; Langyan, Sapna; Bhushan, Bharat; Rakshit, Sujay (Frontiers in Sustainable Food Systems, 2022)
Development of quality protein maize (QPM)was considered a significant leap towards improvement in the nutritional status of rural masses in developing countries. The nutritional quality of QPMisattributed to the higher concentration of essential amino acids, particularly lysine and tryptophan in its kernel endosperm. However, similarity inthe grains ofQPM and normal maize necessitate the development of a standard protocol to assess the protein quality of maize. The present study aimed at improving the protocol of protein quality assessment in QPM. For this purpose, endosperm defatting and protein estimation procedures were re-standardized and optimized with respect to protocol duration and its amenability for high throughput analysis. Unlike normal maize, QPM and opaque-2mutants were completely defatted within 48 hours period. It was observed that tryptophan content, calculated at each defatting interval, increased in the samples defatted for longer duration. No significant differences were observed in the tryptophan content analyzed in the samples defatted for 48 and 72 hours. Moreover, the endosperm protein estimated byusing Bradford method with certain modifications, strongly correlated with the micro-Kjeldahl method (r =0.9). Relative to micro-Kjeldahl method, Bradford method was found to be precise, rapid and hazard-free.The present findings enable a testing protocol of reduced time duration that can be used in resource-poor settings for the determination of protein quality assay in QPM.Overall, the present study effectively helped in reducing defatting time by 24 hours and protein estimation by 3 hours as compared to the already established CIMMYT protocol. This is expected to enable aggregation of high protein quality maize to facilitate its commercialization.